Brain oxygenation declines in elite Kenyan runners during a maximal interval training session - Santos-Concejero, J.; Billaut, F.; Grobler, L.; Olivan, J.; Noakes, T. D.; Tucker, R. (European Journal of Applied Physiology, 2017)
Purpose: The purpose of this study was to characterise the cerebral oxygenation (Cox) response during a high-intensity interval training session in Kenyan runners, and to examine any relationship with running performance. Methods: 15 Kenyan runners completed a 5-km time trial (TT) and a Fatigue Training Test on a treadmill (repeated running bouts of 1-km at a pace 5% faster than their mean 5-km TT pace with a 30-s recovery until exhaustion). Changes in Cox were monitored via near-infrared spectroscopy through concentration changes in oxy- and deoxy-haemoglobin (Delta[O2Hb] and Delta[HHb]), tissue oxygenation index (TOI), and total hemoglobin index (nTHI). Results: The number of 1-km repetitions achieved by the participants was 5.5 ± 1.2 repetitions at a mean pace of 20.5 ± 0.7 km/h. Delta[O2Hb] measured at the end of each running repetition declined progressively over the course of the trial (p = 0.01, ES = 4.59). Delta[HHb] increased during each running bout until the end of the Fatigue Training Test (p < 0.001; ES = 6.0). TOI decreased significantly from the beginning of the test (p = 0.013, ES = 1.83), whereas nTHI remained stable (ES = 0.08). The Cox decline in the Fatigue Training Test was negatively correlated with the speed at which the test was completed (p = 0.017; r = -0.61), suggesting that the best performers were able to defend their Cox better than those of lower running ability. Conclusions: In conclusion, this study suggests that elite Kenyan runners cannot defend cerebral oxygenation when forced to exercise to their physiological limits. This emphasises the critical importance of pacing in their racing success.